Effect of heating surface morphology on the size of bubbles during the subcooled flow boiling of water at low pressure. (October 2015) - Paz, C.; Conde, M.; Porteiro, J.; Concheiro, M.
Highlights: Experimental investigation on the bubble size in subcooled flow boiling of water. An image processing algorithm was developed for bubble detection. The influence of operational parameters and surface morphology on bubble population and size distribution has been studied. A database of the size distribution of the bubbles under different operating conditions are presented. Abstract: An experimental investigation on the forced convective subcooled flow boiling of water was carried out using image processing. Three copper test parts of different roughness were tested at different operational conditions established through a design of experiments, covering bulk velocities from 0.1 m/s to 0.9 m/s, bulk temperature from 76.5 °C to 93.5 °C, and operating pressures from 110 kPa to 190 kPa. The boiling process has been maintained on the nucleate regimen varying heat flux from 0.1 MW/m 2 to 1 MW/m 2, though image processing was only feasible below 0.65 MW/m 2 . The result of the experimental work is a database of the size distribution of the bubbles at each experimental point and presented as an electronic annex. The results confirmed that bubbles are generally smaller at higher pressure, higher velocities and higher levels of subcooling. The effect of surface morphology proved to be a very strong factor that is normally ignored by correlations and experimental works. Finally, an analysis of the possibility of the interaction of surface morphology with bubble size is presented.